Site-directed mutagenesis of two aromatic residues lining the active site pocket of the yeast Ltp1 - Paoli, Paolo; Modesti, Alessandra; Magherini, Francesca; Gamberi, Tania; Caselli, Anna; Manao, Giampaolo; Raugei, Giovanni; Camici, Guido; Ramponi, Giampietro (Biochimica et biophysica acta, 2007)
We mutated Trp 134 and Tyr 135 of the yeast LMW-PTP to explore their catalytic roles, demonstrating that the mutations of Trp 134 to Tyr or Ala, and Tyr 135 to Ala, all interfere with the formation of the phosphorylenzyme intermediate, a phenomenon that can be seen by the decrease in the kinetic constant of the chemical step ( k 3). Furthermore, we noted that the Trp 134 to Ala mutation causes a dramatic drop in k cat/ K m and a slight enhancement of the dissociation constant K s. The conservative mutant W134Y shows a k cat/ K m very close to that of wild type, probably compensating the two-fold decrease of k 3 with an increase in substrate affinity. The Y135A mutation enhances the substrate affinity, but reduces the enzyme phosphorylation rate. The replacement of Trp 134 with alanine interferes with the partition between phosphorylenzyme hydrolysis and phosphotransfer from the phosphorylenzyme to glycerol and abolish the enzyme activation by adenine. Finally, we found that mutation of Trp 134 to Ala causes a dramatic change in the pH-rate profile that becomes similar to that of the D132A mutant, suggesting that an aromatic residue in position 134 is necessary to assist the proper positioning of the proton donor in the transition state of the chemical step.